Identification of second instar larvae of Panchaetothripinae (Thysanoptera, Thripidae) in Brazil and Argentina - Lima, Élison Fabrício B.; O’donnell, Cheryle A.; Sousa, Yago Lucas C.; Zamar, María Inés (Zootaxa, 2021)
In this paper, we present an illustrated key to second instar larvae of 17 of the 25 Panchaetothripinae species recorded in Brazil and Argentina, several of which are pests of many crops. In addition, comments on morphology and host associations are provided. Heliothrips longisensibilis is recorded for the first time in Argentina.